1984
DOI: 10.1136/hrt.52.6.610
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery disease in Asians in Birmingham.

Abstract: The severity and pattern of coronary artery disease in patients referred for investigation of the disease was compared between Asian and white patients living in Birmingham, matched for age, sex, blood pressure, and duration of symptoms, to investigate the clinical impression that Asians have worse, in particular worse distal, coronary artery disease than whites. Risk factors and outcome were also examined. The coronary angiograms of 34 Asians were compared blindly and repeatedly with those of 68 whites by two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 11 publications
2
18
1
Order By: Relevance
“…Furthermore, the excess mortality in south Asian immigrants steadily increased with decreasing age [8]. Other studies have also reported that south Asians frequently have premature atherosclerosis with more diffuse and aggressive disease than their Caucasian counterparts [7,26].…”
Section: The Prevalence Of Type 2 Diabetes and Cardiovascular Diseasementioning
confidence: 80%
“…Furthermore, the excess mortality in south Asian immigrants steadily increased with decreasing age [8]. Other studies have also reported that south Asians frequently have premature atherosclerosis with more diffuse and aggressive disease than their Caucasian counterparts [7,26].…”
Section: The Prevalence Of Type 2 Diabetes and Cardiovascular Diseasementioning
confidence: 80%
“…The majority of Indo-Asians in the West Midlands come from India and Pakistan; the remainder are from Bangladesh or are Indo-Asians from East Africa [7] . Eighty-eight percent of our Indo-Asian patients originate from the North Indian subcontinent (Punjab and Pakistan).…”
Section: Patientsmentioning
confidence: 99%
“…Furthermore, mortality from coronary heart disease in this group is higher than in the indigenous white Caucasian population, as is the incidence of a further coronary event after the first myocardial infarction [2] . Although the North American literature describes racial differences in the use of invasive procedures in the management of cardiac disease, including coronary artery bypass grafting [2][3][4] , the experience in the United Kingdom does not reflect these differences [2,[5][6][7] . Dissimilarities in the management of cardiac disease, therefore, cannot fully explain the higher mortality in the Indo-Asian ethnic group.…”
Section: Introductionmentioning
confidence: 99%
“…Autopsies also revealed more severe and extensive atherosclerosis and larger infarct size and increased frequency of triple vessel disease among Indians. [2] In CAD, fi rst reported from Singapore in 1959 reveal that people hailing from Indian subcontinent had a higher probability of dying due to CAD. The overall age standardized mortality ratio of CAD in Asian males compared to whites was 37.3% higher in age group of 20-29 years, compared to 36% higher at all ages in the UK.…”
Section: Introductionmentioning
confidence: 99%